2021
DOI: 10.1021/acssuschemeng.0c08708
|View full text |Cite
|
Sign up to set email alerts
|

Double-Phase Heterostructure within Fe-Doped Cu2–xS Quantum Dots with Boosted Electrocatalytic Nitrogen Reduction

Abstract: Electrochemical nitrogen reduction reaction (NRR) is considered as one of the most promising methods for NH 3 synthesis under room temperature and ambient pressure. A grand challenge of NRR is the development of efficient electrocatalysts, for which the delicate nanostructuring of catalysts plays an important role. Herein, a series of Fedoped Cu 2−x S quantum dots (QDs) are synthesized with multiple active sites and interface engineering, in which the double-phase heterostructure plays a key role for boosting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…By adding an Fe precursor during the synthesis of Cu 2− x S quantum dots (QD), Zhang et al synthesized Fe doped Cu 2− x S QD for the NRR. 92 It is found that by controlling the doping amount of Fe, double-phased Cu 2− x S/Cu 5 FeS 4 could be prepared (Fig. 8C).…”
Section: Metal Sulfides For the Nrrmentioning
confidence: 94%
“…By adding an Fe precursor during the synthesis of Cu 2− x S quantum dots (QD), Zhang et al synthesized Fe doped Cu 2− x S QD for the NRR. 92 It is found that by controlling the doping amount of Fe, double-phased Cu 2− x S/Cu 5 FeS 4 could be prepared (Fig. 8C).…”
Section: Metal Sulfides For the Nrrmentioning
confidence: 94%
“…108 Copyright 2021, American Chemical Society current of −1.6 mA and an NH 3 yield rate of 10.27 μg mg −1 h −1 , indicating excellent stability (Figure 12F). Mao et al 108 synthesized an Fe 3% −Cu 2−x S catalyst with multiple active sites via interface engineering. The NH 3 yield of the Fe 3% −Cu 2−x S catalyst is improved to 26.4 μg h −1 mg cat −1 (Figure 12G), corresponding to an FE of 3.1%.…”
Section: Other Fe-non-noble Metal Catalystsmentioning
confidence: 98%
“…During the 10 h test at −1.2 V, CNT@C 3 N 4 –Fe&Cu also exhibited a stable current of −1.6 mA and an NH 3 yield rate of 10.27 μg mg −1 h −1 , indicating excellent stability (Figure 12F). Mao et al 108 . synthesized an Fe 3% −Cu 2−x S catalyst with multiple active sites via interface engineering.…”
Section: Bi‐metallic Fe‐based Catalysts For the Nrrmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen energy holds great potential in renewable energy conversion and storage to meet the challenge of energy crisis, for which novel hydrogen production methods by photocatalytic, electrocatalytic, and photoelectrochemical water splitting into hydrogen and oxygen have attracted tremendous research interest in terms of sustainability and carbon-free considerations . Compared to various methods, photoassisted electrocatalysis (P-EC) emerges as a rising star for hydrogen production by embedding photoactive species, such as plasmonic nanoparticles, , semiconductor nanostructures, , and carbon dots, , directly into various electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%